Chapter Парадокс женского сексуального желания в Преступлении и наказании: к вопросу о женской груди - Dickinson, Sara (Biblioteca di Studi Slavistici, 2023)
The Paradox of Female Sexual Desire in Crime and Punishment: On the Question of the Female Breast . This article examines references to the female breast found in Dostoevsky's novel Crime and Punishment to reveal the contradictory role of female sexuality in his literary world. Despite feminist inclinations and a personal familiarity with "emancipated love," he had particular difficulty with issues of women's sexual desire and female corporeality, associating them with danger. He actively suppressed the bodies and desire of physically attractive women in his work. In Crime and Punishment, for ex., both Sonia and Dunia attract male desire, but do not express their own. References to the female breast in his work reveal this deep ambivalence about the female body: now alluring, now menacing, now subject to torture, the breast can also be symbolically maternal or disease-ridden.